2015
DOI: 10.1371/journal.pone.0128428
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Recordings of Human Microsaccades and Drifts with a Contemporary Video Eye Tracker and the Search Coil Technique

Abstract: Human eyes move continuously, even during visual fixation. These “fixational eye movements” (FEMs) include microsaccades, intersaccadic drift and oculomotor tremor. Research in human FEMs has grown considerably in the last decade, facilitated by the manufacture of noninvasive, high-resolution/speed video-oculography eye trackers. Due to the small magnitude of FEMs, obtaining reliable data can be challenging, however, and depends critically on the sensitivity and precision of the eye tracking system. Yet, no st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 59 publications
(84 reference statements)
3
46
0
Order By: Relevance
“…Some doubts have been previously raised regarding the adequacy of video-oculographic eye trackers for measuring microsaccades (Poletti & Rucci, 2016). However, their performance in detecting miniature fixational eye movements has been found to be comparable to that of the invasive search-coil technique, considered the gold standard in this field (McCamy et al, 2015). Compared with other commercial devices, including the dual-Purkinje-image eye tracker, the EyeLink device has been found to be among the highest in tracking precision (Wang, Mulvey, Pelz, & Holmqvist, 2016).…”
Section: Eye Trackingmentioning
confidence: 99%
“…Some doubts have been previously raised regarding the adequacy of video-oculographic eye trackers for measuring microsaccades (Poletti & Rucci, 2016). However, their performance in detecting miniature fixational eye movements has been found to be comparable to that of the invasive search-coil technique, considered the gold standard in this field (McCamy et al, 2015). Compared with other commercial devices, including the dual-Purkinje-image eye tracker, the EyeLink device has been found to be among the highest in tracking precision (Wang, Mulvey, Pelz, & Holmqvist, 2016).…”
Section: Eye Trackingmentioning
confidence: 99%
“…Some doubts have been recently raised regarding the adequacy of video‐oculographic eye trackers for measuring microsaccades (Poletti & Rucci, ). However, its accuracy and performance in detecting miniature fixational eye movements was found to be high compared to other commercial devices (McCamy et al, ; Wang, Mulvey, Pelz, & Holmqvist, ).…”
Section: Methodsmentioning
confidence: 89%
“…Eye position data were first processed by a digital filter (3rd order Butterworth low‐pass filter with the cutoff frequency of 200 Hz) before the following analyses of ocular drift as well as fixational saccades. We adopted a method used in previous studies to define the periods of ocular drift (Cherici, Kuang, Poletti, & Rucci, ; Di Stasi et al., ; McCamy et al., ; Murakami, Kitaoka, & Ashida, ) (see also Supporting Information Figure S1). Briefly, ocular drift periods were defined as data points between the end and start of (fixational) saccades [see below for (fixational) saccade detection], while 10 ms from the start and end of ocular drift periods was excluded due to potential contaminations of fixational saccades and their overshoots (Moller, Laursen, Tygesen, & Sjolie, ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the estimation of eye positions by video‐based eye trackers is influenced by changes in pupil areas even when subjects maintain eye fixation at the same location (Choe, Blake, & Lee, ; McCamy et al., ). We fitted a second order polynomial of pupil area to eye position and used its residuals as corrected eye positions for the calculation of ocular drift velocity (Choe et al., ).…”
Section: Methodsmentioning
confidence: 99%